KOMUNIKASI ORGANISASI SEBAGAI MOBILITAS SOSIAL - Ninik Hidayati (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Communication within an organization is a common practice for managing relationships between individuals and groups. In an organization is determined by the person's position on the structure and Hierarchy within the organization. Today the organization assigns roles to each member so that the roles are then operationalized into tasks and functions. The process of cooperation in implementing change or acceleration of change within the organization is called "Organizational Communication". Aspects to be known from the group communication is who and how the role of messenger in the group, what messages are exchanged in groups, patterns of interaction that occurs in groups, cohesiveness among members in groups, and what norms should be used in group.